Pregnancy outcomes in thoroughbred mares inseminated with fresh semen from either stallion or jack at foal heat or subsequent estrus - TALLURI, T R; SINGH, CHANDAN; PRAKASH, VED (The Indian Journal of Animal Sciences, 2021)
The current study investigated the effect of different mating (stallion vs jack) and breeding patterns (foal heat vs subsequent estrus) on the outcome of conception and foaling rates in thoroughbred mares. A retrospective study on the reproductive performance of 6,040 artificially inseminated thoroughbred mares during seven consecutive breeding seasons (2010-2017) has been taken into consideration for the current study. Mares were inseminated with fresh semen obtained from eight of each fertile horse stallions (Thoroughbred) and jacks (Poitou breed). The pregnancy status was examined at 30 (P30), 60 (P60) and 90 (P90) days post breeding and pregnancy rate was calculated as number of mares pregnant at 30, 60 and 90 day post-mating, out of total mares mated. Pregnancy Rates (PR) of mares inseminated at the foal heat were higher, but non-significantly different from PR of the subsequent estrus mares which did not become pregnant after artificial insemination (AI) at foal heat and inseminated again at the subsequent estrous cycle. There was also a significant difference in the PR and Fertility rate (FR) in mares inseminated either with stallion semen or with jack semen to produce horse and mule foals respectively. From the data on mares mated with horse stallion semen, higher PR as well as FR was found in comparison to the mares that were inseminated with jack semen. In conclusion, the present study found a significant effect of breeding pattern and mating pattern affecting both PR and FR in thoroughbred mares.